The PBAP chromatin remodeling complex mediates summer diapause via H3K4me3-driven juvenile hormone regulation in Colaphellus bowringi - Zhong Tian; Kou Wang; Shuang Guo; Jia-Xu Li; Kirst King-Jones; Fen Zhu; Wen Liu; Xiao-Ping Wang (Proceedings of the National Academy of Sciences, 2025)
Diapause, a developmental arrest mechanism, helps animals to survive seasonal changes via endocrine regulation. While obligate diapause is genetically programmed, facultative diapause is typically triggered by environmental cues such as photoperiod. In insects, this often leads to reproductive diapause characterized by reduced juvenile hormone (JH) signaling, resulting in ovarian arrest and lipid accumulation. However, the molecular link between photoperiod and hormonal control remains poorly understood. In this study, we investigated the cabbage beetle Colaphellus bowringi as our model system. This species exhibits a photoperiodic response, where short-day (SD) conditions promote reproduction, whereas long-day (LD) conditions induce diapause. Our research identified the PBAP chromatin remodeling complex as a key regulator of LD-induced summer diapause entry. Through RNAi screening of 56 transcriptional regulators that were differentially expressed between SD and LD females, we identified BAP170, a PBAP-specific component, as a key mediator of diapause. Knockdown of bap170 in SD females induced reproductive diapause traits, which were reversed by treatment with methoprene, a JH analog, suggesting that the PBAP complex regulates diapause by influencing JH production. We further demonstrated that the PBAP complex modulates JH biosynthesis via SET1/COMPASS-mediated trimethylation of H3K4. Transcriptome analysis and a second RNAi screen identified calmodulin , a calcium-binding messenger protein gene, as a direct target of PBAP-SET1/COMPASS-H3K4me3 signaling in the corpora allata (CA), the primary source of JH. These findings reveal how the chromatin remodeling machinery translates photoperiod signals into endocrine responses governing seasonal adaptation.